(untitled) (Indian Journal of Child Health, 2014)
The central nervous system is involved in 5-35% children suffering from typhoid fever and manifest asneuropsychiatric features such as confusion, encephalopathy, meningismus, convulsion and focal neurologicaldeficit. However, only few cases of acute disseminated encephalomyelitis (ADEM) have been reported along withenteric fever. ADEM is a monophasic immune-mediated demyelination disorder, which commonly follows viralinfections and vaccination. We here report a case of typhoid fever who later developed ADEM.